Evaluasi Kualitas E-Government Menggunakan Metode E-Govqual, Importance Performance Analysis (IPA) dan Heuristic Evaluation - Wilhelmus Sabatani Jangku; Candiasa, I Made; Sunarya, I Made Gede (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Since the construction of the main website of West Manggarai Regency Government, it has never been evaluated and the level of user satisfaction is unknown. In addition, problems were found related to website functions and interfaces, which indicate that website services have not met expectations, so it needs to be evaluated by measuring the level of user satisfaction. The evaluation combines the E-GovQual method to measure gaps, Importance Performance Analysis to measure the fit between perceptions and expectations and find attributes that need to be improved, and Heuristic Evaluation to analyze the severity of usability problems. The research respondents were 395 website users, calculated using the Slovin formula based on the total population of website visitors. The results of the Gap Analysis obtained an average value of -0.080, which means that the website services did not meet the user expectations. Suitability analysis results obtained an average value of 97.77%, which means that website services have not met user expectations. The quadrant analysis obtained 12 attributes that need to be improved. The results of heuristic analysis through severity assessment found 8 attributes that have usability problems > 0 and 5 new problem findings by evaluators. The results of FGD for these 13 attributes all get improvement solutions implemented in the form of prototypes. The results of the prototype create a better user experience and can increase the effectiveness of the program. The resulting prototype creates a better user experience and can improve government effectiveness and efficiency.